The two‐component systems PrrBA and NtrYX co‐ordinately regulate the adaptation of Brucella abortus to an oxygen‐limited environment. Issue 2 (26th March 2013) - Carrica, Mariela del Carmen; Fernandez, Ignacio; Sieira, Rodrigo; Paris, Gastón; Goldbaum, Fernando Alberto
Summary Brucella is the causative agent of the zoonotic disease brucellosis, which is endemic in many parts of the world. The success of Brucella as pathogen relies in its ability to adapt to the harsh environmental conditions found in mammalian hosts. One of its main adaptations is the induction of the expression of different genes involved in respiration at low oxygen tension. In this report we describe a regulatory network involved in this adaptation. We show that Brucella abortus PrrBA is a functional two‐component signal transduction system that responds to the redox status and acts as a global regulator controlling the expression of the regulatory proteins NtrY, FnrN and NnrA, which are involved in the adaptation to survive at low oxygen tension. We also show that the two‐component systems PrrBA and NtrYX co‐ordinately regulate the expression of denitrification and high‐affinity cytochrome oxidase genes. Strikingly, a double mutant strain in the prrB and ntrY genes is severely impaired in growth and virulence, while the ntrY and prrB single mutant strains are similar to wild‐type B. abortus. The proposed regulatory network may contribute to understand the mechanisms used by Brucella for a successful adaptation to its replicative niche inside mammalian cells.